13. The Acoustic Analysis of Violins and the Artistic Impressions Evaluated by Musicians - Stanciu Mariana Domnica; Nauncef Alina Maria; Dinulică Florin; Mihălcică Mircea; Gliga Vasile Ghiorghe; Nastac Silviu Marian (Sciendo, 2023)
Violin studies can be classified into two main types: psychoacoustic studies, which are based on the artistic perception of audibility by violinists and vibro-acoustic studies, which are based on the spectral analysis of the vibrations and sounds produced by the instruments. The paper presents the acoustic analysis of violins by means of specialized software, their main acoustic characteristics being extracted in the form of frequency spectrum, spectrograms, specific modes and number of harmonics. These results were compared with the results of the opinion poll among musicians regarding the acoustic qualities of violins, based on musical auditions. The results highlighted the fact that the acoustic analysis technique cannot detect in totality the psycho-acoustic effects of musical sounds, therefore the establishment of the acoustic quality of the instruments on objective foundations, since the personal touch of an instrumental artist aims at the approach and articulation of the musical discourse, in a complex manner, combined with the interpretation of forms and styles.